Development of recommendations for a minimum dataset for Identifying Social factors that Stratify Health Opportunities and Outcomes (ISSHOOs) in pain research - Emma L. Karran; Aidan G. Cashin; Trevor Barker; Mark A. Boyd; Alessandro Chiarotto; Vina Mohabir; Jennifer Petkovic; Saurab Sharma; Peter Tugwell; G. Lorimer Moseley (MethodsX, 2024)
There is increasing recognition of the need for researchers to collect and report data that can illuminate health inequities. In pain research, routinely collecting equity-relevant data has the potential to inform about the generalisability of findings; whether the intervention has differential effects across strata of society; or it could be used to guide population targeting for clinical studies. Developing clarity and consensus on what data should be collected and how to collect it is required to prompt researchers to further consider equity issues in the planning, conduct, interpretation, and reporting of research. The overarching aim of the ‘Identifying Social Factors that Stratify Health Opportunities and Outcomes’ (ISSHOOs) in pain research project is to provide researchers in the pain field with recommendations to guide the routine collection of equity-relevant data. The design of this project is consistent with the methods outlined in the ‘Guidance for Developers of Health Research Reporting Guidelines’ and involves 4 stages: (i) Scoping review; (ii) Delphi Study; (iii) Consensus Meeting; and (iv) Focus Groups. This stakeholder-engaged project will produce a minimum dataset that has global, expert consensus. Results will be disseminated along with explanation and elaboration as a crucial step towards facilitating future action to address avoidable disparities in pain outcomes.